Land Development 1985–2023 as a Function of Road Improvement, Employment, and Mobility: A Case Study of Tennessee - Jayanta Biswas; Anzhelika Antipova (Land)
Metaverse environments aim at replicating physical reality at various scales. While the potential growth of digital land is limitless, certain development factors may drive greater growth and lead to changes in surrounding land use and the expansion of developed land. In this study, we are bridging digital and physical world living environments using physical land as an example. Specifically, we focus on Tennessee as a study area and offer a spatial perspective on factors of urban land growth and study the relationship between infrastructure (road) development, employment, mobility, and land use change in the physical world, which may help understand this connection in the digital land and real estate domain. We show a significant role of employment hubs in driving developed land growth (i.e., land development). Economic activity consistently appears significant in urban land expansion, with the land development effect of employment stretching over a larger area well beyond immediate proximity to road infrastructure. Land development is measured in this study by a developed land density in both urban and rural areas. Mobility (measured by VMT) has a weaker impact on land development though still positive and statistically significant. This research is crucial for developing sustainable land growth strategies and informing future transport planning and land-use policies.